Next-generation sequencing of LDLR and APOB genes in patients with a clinical diagnosis of Familial Hypercholesterolaemia - Alves, A.C. (2012)
Familial hypercholesterolemia (FH) is a genetic condition characterized by a high cholesterol concentration in the blood. The most frequent causes of FH are inherited defects in the Low Density Lipoprotein Receptor gene (LDLR) but, in a small percentage of patients, mutations in the apolipoprotein B gene (APOB) and in the propotein convertase subtilisin/kexin type 9 gene (PCSK9) are also responsible for FH. These 3 genes are currently studied in the “Portuguese FH study”. From the 563 families with a clinical diagnosis of FH studied only 41% of these have a mutation in one of the 3 studied genes, so other gene defects must exist to explain the cause of hypercholesterolemia in the remaining families. The aim of this study was the exclusion of previously unidentified LDLR and APOB gene defects in 65 severely affected patients, as well as the exclusion of mutations in LDLRAP1 and CYP7A1 genes in patients with possible recessive hypercholesterolemia. The whole sequencing of LDLR and APOB genes of the 65 index patients, without mutations in LDLR or PCSK9 genes or in fragments of exon 26 and 29 of APOB gene was performed. A pool of the 65 DNAs was sequenced by pyrosequecing with custom design primers and a total of 227688 nucleotide reads were obtained, corresponding to a mean coverage of 35x/fragment/individual. CYP7A1 and LDLRAP1 genes were analysed by PCR and direct sequencing. A total of 87 alterations were detected by pyrosequencing. More than half were previously described SNPs and 32 were novel possible pathogenic variants. The majority of these variants (25) were in exons 26 and 29. From the 32 novel variations identified by pyrosequencing only 4 were found by Sanger sequencing. Three alterations (2 novel and 1 described) were found by Sanger sequencing and were not detected by pyrosequencing. Three SNP’s were also studied do to their low alleles estimated. After family studies of these 10 variants, 3 alterations did not co-segregate in the family, 4 alterations were not possible to verify co-segregation and 3 of the alterations found are possibly mutations causing disease, but functional studies are required to prove pathogenicity. No mutations were found in LDLRAP1 and CYP7A1 genes in 10 patients with possible recessive hypercholesterolemia. Patients, in whom it was not possible to find the genetic cause of the hypercholesterolaemia, will require further studies, since all show a severe clinical phenotype of FH.